IMPLEMENTASI VIRTUAL PRIVATE NETWOR MENGGUNAKAN POINT-TO-POINT TUNNELING PROTOCOL - Eka Satryawati; Dwi Agung Pangestu; Ade Surya Budiman (Institut Teknologi dan Bisnis Swadharma, 2022)
Today's technological development is very rapid, especially in the field of network security. The field of network security is a matter that will be a very important part because the network security system is used to guarantee the confidentiality, theft, or burglary of data on a company. In its implementation, a VPN network (Virtual Private Network) uses a site-to-site Point to Point Tunel Protocol (PPTP) method to connect between two places that are located far apart. The main facility of using PPTP is being able to use a public-switched telephone network (PSTN) to build a VPN. At PT Indosis Integrasi Jakarta, the place where the author conducts research there are several problems that the author found, namely, when sending data between the head office and branch offices in Bandung, there is no security that ensures that the data is safe. With the current state of the network, uninterested parties will easily access or steal confidential company data.